2017
DOI: 10.1016/j.euf.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-risk Features and Effect of Neoadjuvant Chemotherapy in Urothelial Cancer Patients with Invasion into the Lamina Propria on Transurethral Resection in the Absence of Deep Muscle Invasion

Abstract: Background High-risk non–muscle-invasive bladder cancer (NMIBC) that invades into the lamina propria is frequently understaged and is associated with a risk of lymph node metastasis and death. Objective To identify high-risk features (HRFs) for NMIBC that may identify patients with poorer prognosis who may benefit from neoadjuvant chemotherapy (NAC) prior to radical cystectomy (RC). Design, setting, and participants We performed a single-center retrospective review of patients who underwent RC for NMIBC wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…16,17,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][40][41][42][43][44]46,49,51,54,56,57,[61][62][63]65,68,69,[72][73][74][75][76] BCG therapy was an inclusion criterion for some of these studies, which contributed to this high rate. In the remaining 18 studies (30%), the reported use of BCG instillations in HR-NMIBC patients ranged from 3% to 86%.- 18,20,39,45,47,48,50,52,…”
Section: Treatment Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][40][41][42][43][44]46,49,51,54,56,57,[61][62][63]65,68,69,[72][73][74][75][76] BCG therapy was an inclusion criterion for some of these studies, which contributed to this high rate. In the remaining 18 studies (30%), the reported use of BCG instillations in HR-NMIBC patients ranged from 3% to 86%.- 18,20,39,45,47,48,50,52,…”
Section: Treatment Patternsmentioning
confidence: 99%
“…16,17,21,22,[24][25][26][27][28]31,[33][34][35][36][37]40,42,49,51,54,56,57,61,65,68,74,75,77 Among the remaining eight studies, rates of BCG induction therapy ranged from 29% to 95%. 20,45,47,52,59,63,77,78 The use of maintenance BCG in HR-NMIBC was reported in 31 studies, with rates being more variable than those seen with induction therapy. 16,17,[26][27][28][29]31,33,34,36,37,40,42,45,46,[49]…”
Section: Treatment Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin-based neoadjuvant chemotherapy (NAC) is the standard of care in the management of patients with bladder cancer (BCa) who are candidates for radical cystectomy (RC) [1,2]. During the past few decades, several efforts have been spent to identify more active chemotherapy regimens and to enable appropriate patient selection through the use of clinical and genomic predictors of response to chemotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cystectomy is a major surgical and anaesthetic undertaking, with significant cost and quality‐of‐life implications and an overall 90‐day mortality of 4% (ranging from 2% in those aged < 70 years and 9% in those aged >80 years) . NMIBC is also difficult to stage accurately, with recent studies suggesting that high‐risk NMIBC invading the lamina propria is frequently understaged and is associated with a high risk of lymph node metastases and mortality . A substantial proportion of patients who have failed BCG with T1 tumours are upstaged at the time of surgery, with up to 10% found to have lymph node metastases .…”
Section: Introductionmentioning
confidence: 99%